PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TURNAMENT (TGT) DENGAN BANTUAN MEDIA PERMAINAN MONOPOLI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SD MUHAMMADIYAH IDI TELLO BARU - Nur Anisa; Nursalam; Ulfayani Hakim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of the Teams Games Tournament (TGT) learning model assisted by Monopoly game media on the learning outcomes of fourth-grade students at SD Muhammadiyah IDI Tello Baru. The research background is the low learning outcomes of students in the IPAS subject, which is caused by monotonous learning methods and a lack of creative media. This research used a quantitative method with a pre-experimental approach and a One Group Pretest-Posttest Design. The population was all 215 students of SD Muhammadiyah IDI Tello Baru, with a sample of 22 fourth-grade students selected using a random sampling technique. Data were collected through pretest and posttest and analyzed using descriptive statistics and a paired samples t-test with SPSS version 30. The results showed a significant increase in students' learning outcomes. The average pretest score was 57.14, which increased to 82.32 in the posttest. The hypothesis test results showed that the value of tcount​>ttable​ (8.452 > 1.721) and a Sig. (2-tailed) value of < 0.001, which is less than 0.05. This indicates that the Teams Games Tournament (TGT) learning model assisted by Monopoly game media has a significant effect on the learning outcomes of fourth-grade students in the IPAS subject at SD Muhammadiyah IDI Tello Baru. This research proves that using the TGT model with Monopoly media can make learning more effective, interactive, and fun.